Schools Literacy Movement in Innovation of Language Curriculum Development - Novita Efendi; Diki Atmarizon (Postgraduate School, Universitas Negeri Padang, 2022)
Innovations and changes have been made to the Indonesian curriculum since 2013. These changes aim to improve the quality of education in Indonesia. The curriculum currently used to learn Indonesian is text-based. Several years later, the government launched the School Literacy Movement (GLS) to realize the vision and mission so that people can adapt to developments in information and technology by updating them in the National Literacy Movement (GLN). The purpose of this study was to find out the literacy activities carried out in schools as well as see the responses from students after completing literacy activities. This study recommends handling literacy as an innovation in curriculum development in schools. This research is a descriptive study using structured interview techniques and questionnaire collection techniques using interview guidelines and questionnaires as working tools. Interviews were conducted with five Indonesian teachers in West Sumatra and 30 students were asked to answer a questionnaire. The results of the study show that in practice literacy is not carried out by the rules so literacy goals are not achieved properly. In practice, curriculum and literacy appear as two different things and their implementation is inconsistent. Learning activities are always related to literacy activities. Particularly in language learning, literacy activities in reading and writing are very important things to be carried out by each component of the school.